1993
DOI: 10.1089/hum.1993.4.5-609
|View full text |Cite
|
Sign up to set email alerts
|

Increased Viral Titer Through Concentration of Viral Harvests from Retroviral Packaging Lines

Abstract: Dependent on the viral vector and the specific assay used, viral titers produced from commonly used retroviral packaging cell lines have an upper limit in the range of 10(5) to 10(7) infectious units/ml. We have developed a generally applicable method, using hollow-fiber filtration technology, which allows for the concentration of infectious virus derived from packaging lines. This method resulted in a reproducible 10- to 30-fold increase in viral titer and can readily be scaled to accommodate larger input vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 29 publications
3
67
0
Order By: Relevance
“…Other approaches include: (1) the development of optimized conditions of ome of target cells makes them effective gene transfer vehicles for the introduction of foreign genes into a broad retroviral production and transduction; 9,10 (2) concentration of retrovirus particles from cell-free supernatant range of cell lines. The delivery of therapeutic gene(s) into target cells using retroviral vectors has been achieusing hollow-fiber filtration technology; 11 and (3) screening of retroviral packaging cell lines using high selection ved in cultured cells and more recently ex vivo in clinical settings. 1 The efficiency with which genes can be intropressure.…”
mentioning
confidence: 99%
“…Other approaches include: (1) the development of optimized conditions of ome of target cells makes them effective gene transfer vehicles for the introduction of foreign genes into a broad retroviral production and transduction; 9,10 (2) concentration of retrovirus particles from cell-free supernatant range of cell lines. The delivery of therapeutic gene(s) into target cells using retroviral vectors has been achieusing hollow-fiber filtration technology; 11 and (3) screening of retroviral packaging cell lines using high selection ved in cultured cells and more recently ex vivo in clinical settings. 1 The efficiency with which genes can be intropressure.…”
mentioning
confidence: 99%
“…Efforts to concentrate retroviruses using centrifugation 28 and tangential filtration 29,30 showed that target cell transduction rate increases proportionally with the virus titer. Kitten et al 31 described a high-producer cell line (10 8 ffu/ml) transducing 46 ± 17% of rat hepatocytes with retrovirus bolus-injected through the portal vein, without any concentration step.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, diminution of retroviral infectivity during the process of concentration (ie, ultracentrifugation) and purification (ie, ultrafiltration) has been reported. 25,26 This is because the association of gp70 (binding to cellular receptor) and p15E (fusion with plasma membrane) subunits of type C retroviral envelope protein is a labile disulfide linkage, which is not robust under shearing forces. 27,28 Owing to the loss of gp70 subunit (or SU domain), the retrovirus cannot enter the target cell via receptor-mediated endocytosis.…”
Section: Enhanced Retroviral Gene Deliverymentioning
confidence: 99%